Daurah Fikih Salat di Pondok Pesantren Ibnu Qayyim Bone sebagai Upaya Melahirkan Generasi Unggul - Sirajuddin; Saifullah bin Anshor; Muhammad Nirwan Idris (WAHATUL MUJTAMA': Jurnal Pengabdian Masyarakat, 2021)
Ibnu Qayyim Islamic Boarding school is a formal educational institution, located in Walannae Village, Tanete Riattang Subdistrict, Bone Regency.This boarding school has two levels of education, namely Integrated Islamic Junior High School (SMP IT) Technology and Vocational High School (SMK) with the department of Network Computer Engineering. The purpose of KKN STIBA Makassar class IV is to carry out community service which is one of the tri dharma pillars of higher education. The method of community service implementation in the cottage begins with mapping the problems and needs of students by using instruments made independently combined with SOAR analysis. After conducting a needs analysis, the next stage is the preparation of an adaptive work program with cottage conditions. Among the work programs implemented by students of KKN STIBA Makassar class IV is Daurah Fikih Salat. The result of the implementation of this KKN is the improvement of the understanding of students around taharah and prayer that is seen in the ordinances of wudoo' and prayer movements that are getting better and right.